A low prevalence of mycobacteria in freshwater fish from water reservoirs, ponds and farms - Mrlík, Vojtěch; Slaný, Michal; Kubecka, J; Seda, J; Nečas, Alois; Babák, Vladimír; Slaná, Iva; Kříž, P; Pavlík, Ivo (Journal of fish diseases, 2012)
A survey of the occurrence of mycobacteria was conducted from 717 freshwater fish (25 species) in two water reservoirs, five ponds and two farms in the Czech Republic. A total of 2182 tissue samples from these fish were examined using the conventional culture method. Thirteen mycobacterial isolates were obtained from 12 (1.7%) fish belonging to nine species. Isolates were identified using sequence analysis of the 16SrRNA gene as: Mycobacterium algericum, M. fortuitum, M. gordonae, M. insubricum, M. kumamotonense, M. nonchromogenicum, two isolates of M. peregrinum, M. terrae and M. triplex. Mycobacteria were isolated more frequently from fish skin and gills than from internal organs or muscles.
Keywords: Czech Republic; Česká republika; Fishes; rybníky; Ponds; prevalence; nemoci ryb; zvířata; Animals; Mycobacterium Infections; mykobakteriózy; RNA, Ribosomal, 16S; Fresh Water; ryby; sladká voda; Prevalence; Mycobacterium; Fish Diseases; RNA ribozomální 16S